QUALITY ANALYSIS OF THE JAKARTANOTEBOOK.COM WEBSITE USING WEBQUAL 4.0 - Megantari Putri Gunadinnusa; Dani Hamdani (STMIK Pringsewu Lampung, 2020)
E-commerce has become a fairly developed concept in the field of technology today. In addition to providing convenience and advantages compared to conventional shopping concepts, including all the desired information, consumers can be accessed in more detail, quickly without being limited by place and time, and the transaction process can be done more easily. Competition among competitors in the field of e-commerce has been overwhelming and competing with each other in innovation to be superior in the market. This study will conduct a quality test of one e-commerce company using the WebQual method. In its implementation with this method to measure quality on a website based on the observation of the questionnaire to the user as a source of data. The results of this study will conclude a number of factors that are very important to customer satisfaction to be evaluation advice for the company.